2022
DOI: 10.1029/2022jd037301
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate‐Volatility Organic Compounds Observed in a Coastal Megacity: Importance of Non‐Road Source Emissions

Abstract: Secondary organic aerosols (SOAs), which can account for 20%-95% of organic aerosols (OAs), significantly impact the global climate, regional air quality, and human health (Huang et al., 2014;Pöschl, 2005;Zhang et al., 2007). SOA remains the least understood composition of OA, and atmospheric models that only consider volatile organic compounds (VOCs) as SOA precursors significantly underestimate the SOA formed both in field observations and chamber experiments (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 89 publications
(185 reference statements)
0
6
0
Order By: Relevance
“…Recent studies have shown that semi-/intermediate-VOCs (S/IVOCs) contributed significantly to SOA with generally higher SOA yields than VOCs (Robinson et al, 2007). A higher fraction of S/IVOCs and a higher SOA yield have been found for ship emissions when compared to other sources (Fang et al, 2022;Huang et al, 2018b). In this study, S/IVOCs were not measured and only VOCs were included for the calculation of SOAPF.…”
Section: Contribution Of Ship Emission To Vocs and Soa/o 3 Formation ...mentioning
confidence: 98%
See 3 more Smart Citations
“…Recent studies have shown that semi-/intermediate-VOCs (S/IVOCs) contributed significantly to SOA with generally higher SOA yields than VOCs (Robinson et al, 2007). A higher fraction of S/IVOCs and a higher SOA yield have been found for ship emissions when compared to other sources (Fang et al, 2022;Huang et al, 2018b). In this study, S/IVOCs were not measured and only VOCs were included for the calculation of SOAPF.…”
Section: Contribution Of Ship Emission To Vocs and Soa/o 3 Formation ...mentioning
confidence: 98%
“…The reaction rates of VOCs with O 3 and NO 3 radical are slow. Therefore, the initial concentrations of VOCs were calculated only considering reactions involving OH radicals, as described by the following equations (Fang et al., 2022; Z. Zhang et al., 2016): Ciobserved=Ciinitial×exp)(ki[OH]Δnormalt ${\left[{C}_{i}\right]}_{\text{observed}}={\left[{C}_{i}\right]}_{\text{initial}}\times \mathrm{exp}\left(-{\mathrm{k}}_{i}[\text{OH}]\Delta \mathrm{t}\right)$ [OH]Δt=1kXkE×)(ln[normalX][normalE]0ln[normalX][normalE]t $[\text{OH}]\Delta t=\frac{1}{{\mathrm{k}}_{\mathrm{X}}-{\mathrm{k}}_{\mathrm{E}}}\times \left(\mathrm{ln}{\left(\frac{[\mathrm{X}]}{[\mathrm{E}]}\right)}_{0}-\mathrm{ln}{\left(\frac{[\mathrm{X}]}{[\mathrm{E}]}\right)}_{t}\right)$ where [ C i ] observed (μg m −3 ) is the observed concentration of species i ; [ C i ] initial (μg m −3 ) is the initial concentration of species i ; k i (cm −3 molecule −1 s −1 ) is the rate constant for the reaction of species i with OH radicals. In this study, a highly significant correlation ( r 2 = 0.89, p < 0.01) was identified between m/p‐xylene (X) and ethylbenzene (E).…”
Section: Field Observations and Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Mobile source emissions are a significant source of full-volatility organics and contribute to SOA formation. Previous studies have been conducted on mobile source emissions of VOCs ,, and I/SVOCs. , In recent years, with the implementation of effective control of on-road mobile source emissions in China, pollution from nonroad mobile sources has become more prominent. Zhao et al found that lower holding nonroad mobile sources emitted comparable amounts of IVOCs to on-road vehicles in China (2017). NRAM accounts for a large share of hydrocarbon (HC) emissions from nonroad mobile sources, while few studies have been conducted on their VOCs or I/SVOCs and the simultaneous testing of full-volatility organics .…”
Section: Introductionmentioning
confidence: 99%